A hybrid thermo‐kinetic model for high temperature plasma gasification. Issue 7 (13th March 2018) - Verma, Babita K.; Rajeshkannan, E.; Renganathan, T.; Pushpavanam, S.
Abstract : Plasma gasification is a process intensification technique in which the prevailing high temperatures accelerate the reactions resulting in a significant size reduction of the gasifier. Conventionally, a gasifier is modeled using either a thermodynamic or a kinetic approach. Present work proposes a novel method of modeling the plasma gasification process which combines these two approaches. The process is modeled as a combination of two regions: a Plasma Gasifier Zone (PGZ) and a Quenching Zone (QZ). PGZ, where gasification of feedstock takes place at high temperatures is modeled by thermodynamic equilibrium. QZ, where the syngas produced in the PGZ cools down, is modeled by kinetic approach. The hybrid approach captures the behavior more accurately and requires less computational effort. The proposed hybrid model is validated with experimental data from literature. The model is used to analyze the influence of radicals in plasma gasification and the performance for different operating conditions. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2592–2602, 2018